2019
DOI: 10.4238/gmr18104
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Colored fiber cotton in the Uberlândia region using artificial neural networks for yield assessment

Abstract: Cotton is the most widely utilized natural fiber in the world. Brazil is currently one of the world's largest cotton producers. Cotton crops are cultivated in all regions of the country, especially in the Cerrado biome. Studies of genotype x environment (GxE) interactions evaluate the adaptability and stability of cotton genotypes. Adaptability and stability evaluations help understand genotype responses to environmental stimuli and the predictability of genotypes in their response to environmental oscillation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Another relevant point is that ANNs are not only based on means and variances (Cruz and Nascimento 2018), but also increase the number of observations and reduce the apparent error rate, quantifying the weights between neurons (Cardoso et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Another relevant point is that ANNs are not only based on means and variances (Cruz and Nascimento 2018), but also increase the number of observations and reduce the apparent error rate, quantifying the weights between neurons (Cardoso et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Hu et al (2019), analyzing the cotton yarn quality prediction model based on the artificial recurrent neural network, found that the experimental results show better accuracy. Cardoso et al (2019), found greater efficiency of ARR for studies of adaptability and stability in cotton, when compared to conventional statistics.…”
Section: Use Of Computational Intelligence In the Genetic Divergence Of Colored Cotton Plantsmentioning
confidence: 98%
“…This naturally colored cotton is important since the fiber does not need to be dyed, eliminating the use of water and reducing production costs (Dutt et al 2008). However, these fibers are of low quality when compared to white fibers, and therefore research into genetically improving the plants is required (Cardoso 2019).…”
Section: Use Of Computational Intelligence In the Genetic Divergence Of Colored Cotton Plantsmentioning
confidence: 99%
See 2 more Smart Citations